UPAYA KOMUNITAS DALAM MENCEGAH SEKS PRANIKAH DI KALANGAN REMAJA MODERN DI SMK PGRI BANJARBARU - Amelia Rahma; Muhammad Hapi; Aninditya Prahesti; Araya Maharani; Fitriani; Salma Nida Oktaria; Anggun Wulandari (Jurnal Abdi Insani, 2026)
Adolescents are a vulnerable age group prone to making impulsive decisions, including in the context of sexual behavior. The lack of reproductive health education in schools causes many students to have inadequate understanding of the risks of premarital sex. Yet, this behavior can have serious impacts on adolescents' physical, psychological, and social well-being. Therefore, an effective and engaging educational intervention is necessary for this age group. This activity aimed to increase the knowledge and awareness of students at SMK PGRI Banjarbaru about the risks of premarital sexual behavior. The method used was interactive counseling with a participatory approach, including material presentations, discussions, and pre-test and post-test evaluations to measure knowledge improvement. The results showed a significant increase in knowledge among almost all participants, as indicated by higher post-test scores compared to pre-test scores. No student experienced a decrease in score. Discussions were active, demonstrating students' engagement in understanding the material and relating it to real-life situations. The counseling also encouraged students to be more open and critical in facing social pressures related to sexual behavior. In conclusion, interactive counseling proved to be effective in increasing students’ knowledge of premarital sex risks and created a healthy and educational space for adolescents.